Evaluating age and temporal trends of chlorinated paraffins in pooled serum collected from males in Australia between 2004 and 2015. (April 2020) - van Mourik, Louise M.; Toms, Leisa-Maree L.; He, Chang; Banks, Andrew; Hobson, Peter; Leonards, Pim E.G.; de Boer, Jacob; Mueller, Jochen F.
Abstract: Chlorinated paraffins (CPs) are high production volume chemicals of which some show resistance to environmental degradation, long-rang transport, bioaccumulation and toxicity potential. Information regarding their presence in humans is limited, including their human bioaccumulation potential. The present study aimed to evaluate CP levels in human serum from Australia in order to better understand their exposure and current pollution status as well as trends associated with age and time between 2004 and 2015. For this, we selected a male sub-group of the Australian population under 60 years old ( n = 16 pools, total 1600 serum samples). While long-chain CP (C18-20 ) and most short-chain CP (C10-13, SCCPs) levels were below method detection limits (MDL), medium-chain CPs (C14-17, MCCPs) were found in most serum samples (detection frequency 94%) as well as CPs with a carbon chain length of nine (detection frequency 76%). The levels of ΣSCCPs and ΣMCCPs ranged from <MDL−140 and <MDL-520 ng/g lipid weight (lw), respectively, with a median value of 97 ng/g lw for SCCPs and 190 ng/g lw for MCCPs. Analysis by age stratification did not identify any trends but an increase of a factor of 2 in MCCPs levels was observed over time (p < 0.05). Plotting the MCCP/SCCP ratio of all available data in humans over time showed also an increasing trend, including for China. The reported levels are relatively low considering the levels reported in environmental media from Australia such which raises the question to what extent CPs accumulate in humans. Future studies on this aspect are required. Highlights: CPs levels were evaluated in pooled serum collected from mainly males in Australia. MCCPs and CP-C9 levels were found in most pools (detection frequency of 94 and 76%). Analysis by age stratification did not identify any trends. An increase in MCCPs levels was observed over time (2004–2015). The relatively low levels raise the question of how CPs behave in humans.